Information Needs: A Conceptual Investigation - Mahapatra, R. K. (Journal of Information and Knowledge, 2002)
Discusses in detail the importance of ’information needs’ as a concept in the library environment and elaborates the theoretical and conceptual analysis on ’information needs’ as a tool in user study. Explains the views expressed by different experts on the topic. Also briefly analyses the factors affecting needs, types of information needs and the en vironmental aspects which are responsible for developing a systems approach of information needs.